Lepidoptera collected in southern and southwestern Mongolia during expeditions in Mongolian Altai and Gobi Altai in 2022-2023 (Lepidoptera: Bombycoidea, Noctuoidea) - Ilya A. Makhov; Alexej Yu. Matov; Vladimir A. Lukhanov (SHILAP, 2024)
A brief historical outline of lepidopterological research in Mongolia is presented. An annotated checklist of Sphingidae, Notodontidae, Erebidae, Nolidae and Noctuidae collected during 2022 and 2023 in southern and southwestern Mongolia is provided. In total 6 species of Sphingidae, 2 species of Notodontidae, 37 species of Erebidae, 1 species of Nolidae and 119 species of Noctuidae are recorded. Eleven species are recorded as new for the fauna of Mongolia: Hypocala subsatura Guenée, 1852, Eublemma fugitiva (Christoph, 1877), Nola acutula Püngeler, 1902, Cucullia aksuana Draudt, 1934, C. vicina A. Bang-Haas, 1912, Lacanobia praedita (Hübner, [1813]), Hadena intensa Boursin, 1962, H. filograna (Esper, 1788), Lasionycta buraetica Kononenko, 1988, Dichagyris ulrici (Corti & Draudt, 1933), Euxoa uigurica Gyulai, Ronkay & Varga, 2002. Habitus is illustrated for ten of these species. Four Noctuidae species were DNA-barcoded, COI sequence of Xenophysa sharhu Varga, 1989 is published for the first time